Compassionate use of convalescent plasma for treatment of moderate and severe pneumonia in COVID-19 patients and association with IgG antibody levels in donated plasma. (September 2020) - Maor, Yasmin; Cohen, Daniel; Paran, Nir; Israely, Tomer; Ezra, Vered; Axelrod, Ofra; Shinar, Eilat; Izak, Marina; Rahav, Galia; Rahimi-Levene, Naomi; Bazofin, Baruch M; Gelman, Ram; et al.
Abstract: Background: We assessed outcome of patients with moderate and severe COVID-19 following treatment with convalescent plasma (CP) and the association with IgG levels in transfused CP. Methods: A prospective cohort study. Primary outcome was improvement at day 14 defined as alive, not on mechanical ventilation, and moderate, mild, or recovered from COVID-19. Antibody levels in CP units were unknown at the time of treatment. IgG against the spike protein S1 was subsequently measured by ELISA. Neutralizing antibodies titers were determined in a subset. Outcome was assessed in relation to the mean antibody level transfused to the patients (≤4.0 versus >4.0). Findings: Of 49 patients, 11 (22.4%) had moderate, 38 (77.6%) had severe disease, 28 were ventilated. At day 14, 24 (49.0%) patients improved, 9 (18.4%) died, and 13 (26.5%) were ventilated. In 14/98 (14.3%) CP units IgG was < 1.1 (cutoff calibration) and in 60 (61.2%) ≤4.0. IgG level and neutralizing antibody titer were correlated (0.85 p  < 0.001). In patients receiving ≤4.0 antibody levels, 11/30 improved (36.7%) versus 13/19 (68.4%) in patients receiving >4.0 odds ratio (OR) 0.267 [95% confidence interval (CI) 0.079–0.905], P  = 0.030. In patients diagnosed >10 days prior to treatment, 4/14 (22.4%) improved in the ≤4.0 antibody group, versus 6/7 (85.7%) in the >4.0 antibody group, OR 0.048 (95% CI, 0.004–0.520), P  = 0.007. No serious adverse events were reported. Interpretation: Treatment with CP with higher levels of IgG against S1 may benefit patients with moderate and severe COVID-19. IgG against S1 level in CP predicts neutralization antibodies titers.